Дослідження методів забезпечення параметрів якості послуг IoT 5G - Радченко, В. В.; Сабурова, С. О. (ХНУРЕ, 2020)
The Internet of Things can be considered as a global network infrastructure consisting of many connected devices that use touch, communication, network and information technologies.The introduction of IoT 5G services will take the prevailing approach to setting the level of service based on the quality of service provided by the subscribers themselves. Based on these requirements, the operator will form the initial parameters that determine the desired level of quality of service.